Dung removal by dung beetles (Coleoptera: Scarabaeidae) and macrocyclic lactone use on cattle ranches of Yucatan, Mexico - Basto Estrella, Gertudis S. (2016)
The expanded use of macrocyclic lactones (ML) to treat endo- and ectoparasites in cattle in tropical regions, can reduce dung beetle populations, and thus interrupt the dung removal process in cattle pasture ecosystems. During the reproductive period (the rainy season) of two functional groups of dung beetles (paracoprid and telocoprid Scarabaeinae), we compared dung removal amount in ranches where ML are and are not used in Yucatan, Mexico, through exclusion traps baited with 500 g of ML-free cow dung. On each ranch, two transects (separated by 500 m) with six traps each, were set up for 24 hours. After this time, all the dung remnants in each trap were obtained and weighed in order to record the dung removal. Results showed that dung removal amounts were similar in ranches with and without ML use. Dung beetles removed 40.1 % of all cow dung weighed. Paracoprids removed 87.46 % and telocoprids 12.54 % of all the dung that was removed. Our results indicated that the ecological function of dung beetles in the pastures studied, does not seem to be affected by the ML use, and that paracoprid species removed most of the dung. For both types of ranch, further studies that take into account the population dynamics and movement of the most important dung beetle species in the region are required, coupled with laboratory studies evaluating the effect of ML on their reproductive success. This could give some light on the effect of ML on the ecological function of this important insect group in the sustainability of cattle production systems.